The Endogeneity of the Optimum Currency Area Criteria, Intraindustry Trade, and EMU Enlargement - Jarko Fidrmuc (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2001)
This paper tests the endogeneity hypothesis of OCA criteria (Frankel and Rose, 1998) in a cross-section of OECD countries between 1990 and 1999. It is shown that intraindustry trade actually causes the convergence of business cycles, while there is no direct relation between business cycles and bilateral trade intensity. As far as intraindustry trade is positively correlated with trade, the OCA endogeneity hypothesis is confirmed, although the argumentation follows Krugman (1993). Finally, the endogeneity of OCA criteria implies a comparable degree of business cycle hfirmonization of CEECs with EU countries as for the current members for the medium tfirm.
Keywords: F15; F41; 330; Optimum currency area; EMU; trade; business cycle; CEECs; Europäische Wirtschafts- und Währungsunion; Optimaler Währungsraum; Intraindustrieller Handel; EU-Erweiterung; Konjunktur; EU-Staaten; Osteuropa; OECD-Staaten